Solving Euclidean minimal spanning tree problem using a new meta-heuristic approach: Imperialist Competitive algorithm (ICA) - Hosseini, S. M.; Khaled, A. A.; Jin, M. (2012 IEEE International Conference on Industrial Engineering and Engineering Management, 2012)
The minimum spanning tree (MST) problem has numerous applications in design of communication, computer and transportation networks. This paper proposes an application of a new meta-heuristic called Imperialist Competitive algorithm (ICA) for solving a special case of MST defined on a Euclidean plane, called the Euclidean minimum spanning tree (EMST) problem. ICA is inspired by human's socio-political evolution. The solution quality and speed of the proposed are verified by numerical examples compared to a commercial optimization solver.